THE USE OF MIND MAPPING TECHNIQUES IN TEACHING WRITING TO EIGHT GRADE STUDENTS USING GOOGLE MEET PLATFORM VIEWED FROM THEIR CREATIVITY - Chrissy Andrea Putri; Ngadiso Ngadiso; Lidwina Sri Ardiasih (Magister Scientiae, 2023)
Writing accelerates students' use of the target language, making it an essential part of classroom preparation. Writing skills can be improved through the use of mind mapping. The following are the research's goals:1) to determine whether teaching writing to eighth-graders using mind mapping or peer review is more effective, 2) to determine whether eighth-graders with higher levels of creativity have better writing skills than those with lower levels of creativity, and 3) to determine whether teaching methods and students' creativity interact when teaching writing to eighth-graders. An experimental study with a 2x2 factorial design is this one. This study uses 48 students as samples. In this study, writing and creativity tests are used to collect data. ANOVA and the Tukey test are used to analyze the data. The data analysis revealed that the mind mapping method is more effective than the peer review method for teaching eighth-grade writing. In the eighth grade, students with high creativity have better writing skills than students with low creativity. There is an interaction between teaching techniques and students' creativity in teaching writing in the eighth grade.